Heavy metals in soil from bauxite mining area of Kuantan, Malaysia - Syed Ismail, Sharifah Norkhadijah; Zainal Abidin, Emilia; Praveena, Sarva Mangala; Rasdi, Irniza; Mohamad, Syukriah; Wan Ismail, Wan Muhamad Isharman (2017)
The community in the surrounding was reported serious air pollution from bauxite dust and residue that were released by the processing plants and during transportation around Bukit Goh, Gebeng and Kuantan Port, Malaysia. Bauxite contains trace quantities of mercury, hydrated aluminium oxides, hydrated aluminosilicates, iron oxides, titanium oxide, silica and other heavy metals. To measure heavy metals content in deposited soil in the settlement near bauxite mining area of Kuantan. Soil dust was grabbed in two sites near the mining area from December 2015 to February 2016. Samples were analysed with X-ray fluorescence (XRF) (HD Rocksand101). Analysis has detected 36 elements in the soil samples (N = 40). The highest non-carcinogenic element detected was Fe (194,912.75 ± 30,229.31 ppm) followed by Si (160,170.50 ± 41,784.35 ppm), Ti (26,740.40 ± 3,485.32), Ca (4,672.35± 4,042.28 ppm), Mn (1,551.65 ± 954.83 ppm) and Ba (1,260.88 ± 1,523.29 ppm). Mo (597.95 ± 82.05 ppm), Zn (212.90 ± 97.76 ppm) and Hg (36.33 ± 59.47 ppm) also was highly detected. Six carcinogenic elements detected were Cr (480.30 ± 61.47 ppm), Ni (87.30 ± 52.88 ppm), Pb (108.06 ± 78.88 ppm), As (25.17 ± 37.48 ppm), Cd (4.61± 0.78 ppm) and Se (1.87 ± 0.28 ppm). Traces elements with prominent value were Pr (534.29 ± 37.77 ppm), V (524.35 ± 71.00 ppm), Ce (222.95 ± 70.70 ppm), Nd (202.94 ± 79.89 ppm), Hf (91.24 ± 18.78 ppm) and Y (31.16 ± 14.84 ppm). Bauxite mining activity has impacted the soil in the studied area and produced probable health risk effects from the exposure.